The reciprocal effects of architecture and tourism: the sustainability approach / Ali Khaksar ... [et al.] - Khaksar, Ali; Tahmouri, Ali; Hoseinrazavi, Sarvenaz (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2010)
Life, work, recreation, rest and leisure are in fact the activities that occur in places which are usually designed by architects. The positive and negative views and functions of a building will have direct effects on the world ecology; therefore architecture, like many other sciences, hopes to find new solutions for appropriate human life. Sustainability concept and sustainable development in architecture, introduces a new subject labeled “sustainable architecture”. The most important issues of this subject are “eco-tech architecture” and “green architecture” which can play an important role in tourism development across the globe. In this regard, architectural sites and buildings can play an important role in attracting more tourists while at the same time providing good services in accommodation facilities such as hotels, motels, camps and inns, where people can comfortably stay and have eye-catching views. However, with careful consideration and respect to the concept of sustainability in the processes of designing and constructing structures such as museums, towers, bazaars, city hall and opera houses, these places can attracts more tourists and visitors. Consequently tourism can be considered as a means of making architectural works both valuable to visitors as touristic subjects and also economical to conserve and maintain by public or private sector. Furthermore, sustainable architecture is considered to be an environmentally friendly activity since it is considered to be: “the management of a clean and decent environment based on efficient use of natural resources and respect for ecological principles”. The conservation of the environment, respect for the natural resources, realizing the real value and appropriate use of the resources and the environment are the common goal of sustainable architecture and tourism development planning in regard to sustainable development of a country or a region. Iran, as a country with a long history and many architectural buildings and sites, is an excellent example for the purpose of this study. This paper discuss some of the cases.